Efectos de tres concentraciones de fertilizantes en el crecimiento vegetativo de Pinus radiata D. Don, en condiciones de vivero en el sector de Itulcachi, parroquia Pifo, Provincia de Pichincha. - Burgos Guerra, José Andrés (2019)
The objective of this research was to evaluate the effect of three fertilizer evaluations on the initial growth of P. radiata, in nursery conditions. For this, a Completely Random Design (DCA) is established, with three treatments. T1 = Increase in fertilization dose by 25% in relation to control, T2 = Decrease in fertilization dose by 25% in relation to control, T3 = Control. Each treatment consisted of 3 repetitions (2880 plants per treatment). From 45 days after the seeds were sown, the data were calculated, such as height and diameter, crown diameter, vigor index and survival rate. The highest average height was 5.34 cm belonging to treatment 1 and superior to those generated in treatments 2 and 3 (5.29 cm and 5.21 cm respectively), but treatment 2 despite showing a lower height value was the one who had a better performance in the variables of cup diameter (1.66 cm) and survival (48.76%), but also the same average diameter (0.10 cm) as all treatments , and also the one that had a higher percentage of gain compared to treatment 1 and 2, taking into account that there were only specific statistical differences in the survival variable and in height at day 66. Keywords: Fertilizers, Vigor index, Height, Diameter, Dose.